2007
DOI: 10.1210/jc.2007-0297
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Replacement for Central Hypothyroidism: A Randomized Controlled Trial Comparing Two Doses of Thyroxine (T4) with a Combination of T4 and Triiodothyronine

Abstract: Background: Dosage of T 4 in central hypothyroidism is primarily guided by the free serum T 4 level (fT4). However, the optimum fT4 range is ill defined, and subtle hypothyroidism might be missed using this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 38 publications
2
49
0
8
Order By: Relevance
“…In children with documented mild CH and short stature, increasing serum FT 4 from the lower third to near the upper third of the normal reference interval during 6 months significantly increases growth velocity (108 4 to be in the mid-normal or in the upper part of the reference range, which was supported in another study (111). In this study, it was observed that CH patients on empirical T 4 doses (1G0.05 mg/kg per day) had worse outcome in terms of BMI, total-, LDL-, and HDL-cholesterol than patients on a body weight-guided dosing (1.6 mg/kg per day) (111).…”
Section: Central Hypothyroidismmentioning
confidence: 54%
See 1 more Smart Citation
“…In children with documented mild CH and short stature, increasing serum FT 4 from the lower third to near the upper third of the normal reference interval during 6 months significantly increases growth velocity (108 4 to be in the mid-normal or in the upper part of the reference range, which was supported in another study (111). In this study, it was observed that CH patients on empirical T 4 doses (1G0.05 mg/kg per day) had worse outcome in terms of BMI, total-, LDL-, and HDL-cholesterol than patients on a body weight-guided dosing (1.6 mg/kg per day) (111).…”
Section: Central Hypothyroidismmentioning
confidence: 54%
“…In this study, it was observed that CH patients on empirical T 4 doses (1G0.05 mg/kg per day) had worse outcome in terms of BMI, total-, LDL-, and HDL-cholesterol than patients on a body weight-guided dosing (1.6 mg/kg per day) (111). The above dose titration studies, therefore, suggest that FT 4 should be in the upper range of normal, TSH levels should be below 0.1 mIU/l using modern sensitive assays, and the dose of L-T 4 should be targeted at w1.6 mg/kg per day meaning 112 mg per day for a 70 kg person.…”
Section: Central Hypothyroidismmentioning
confidence: 68%
“…impaired quality of life (QOL) (1,2,3). Generally, serum thyroid-stimulating hormone (TSH) level is used as a marker for dose adjustment of L-T 4 replacement therapy (4,5,6).…”
mentioning
confidence: 99%
“…In our patient, once the presence of Central H was confirmed and other entities or critical illness were excluded, and no lesion was found in the MRI and no other hormone was altered, the unusual diagnosis of idiopathic isolated Central H was established, possibly caused by deficient TRH synthesis. 27 Because the optimum thyroxin dose for Central H is still unclear, 28 a dose similar to that given to patients with primary hypothyroidism is recommended (after excluding ACTH deficiency). The main difference in treatment between PH and Central H is that TSH cannot be used to monitor the therapy as it is suppressed to <0.1 mU/L in nearly all patients taking doses of T4 that raise their serum free T4 concentrations to normal.…”
Section: -19mentioning
confidence: 99%